Kualitas Produk dan Pelayanan sebagai Determinan Kepuasan Pelanggan dalam Layanan Transaksi Digital - Muhammad Al Gifari Ramadhan; Halimah Zahrah (Indo Publishing, 2026)
The development of digital transaction services has made customer satisfaction a strategic indicator that is influenced not only by the final success of the transaction, but also by a comprehensive evaluation of the perceived value through product quality and service quality. Along with the increasing dependence of society on technological systems, the relationship between service quality and customer satisfaction has become increasingly complex. Therefore, this study aims to analyze the effect of product quality and service quality on customer satisfaction in digital transaction services. This research uses a quantitative approach with a survey method to obtain consumer perception data. The collected data were then analyzed using multiple linear regression to determine the direction and magnitude of the influence between variables. The results show that both product quality and service quality have a positive effect; however, this effect is not yet significant in directly shaping customer satisfaction. These findings indicate that customer satisfaction in digital transaction services is not only determined by product and service quality, but is also influenced by other supporting factors, such as the smooth functioning of application systems, transaction security, accuracy of service processes, and the ease with which customers use digital platforms. Thus, efforts to improve customer satisfaction in the digital transaction service ecosystem need to be carried out comprehensively, not only through improvements in product and service quality, but also through strengthening system reliability and ensuring consistency in the service experience perceived by customers